Unefulness of a calorie counter which utilizes a one-dimensional accelerometer in measuring the energy expenditure by exercise - Nogami, Harumi; Toyoshima, Hideaki; Hayashi, Senji; Miyanishi, Kunio; Tanabe, Naohito; Tanaka, Akemi; Aomi, Akemi; Funazaki, Toshikazu; Yamagami, Rimiko; Masani, Fumiaki; Aizaki, Toshiya; Shibata, Akira; et al. (Journal of the Japanese Association for Cerebro-cardiovascular Disease Control, 1993)
The number of steps walked and the energy expenditure by exercise were measured in 139 subjects during treadmill exercise test using a pedomoter and a calorie counter utilizing a one-dimensional accelerometer. The work-load energy during the exercise test was calculated from the speed of walking and the slope of the treadmill and used as a standard of comparison with the pedometer readings or calorie counter readings. The protocols for the treadmill test were the Bruce (n= 125) and the Naughton (n=14) methods. The correlation coefficient between the work load calculated energy and the pedomoter readings in all cases was 0.80 and for the calorie counter readings 0.87, the latter tending to be higher than the former (p = 0. 052). Statistical differences in the regression slopes were observed between the two protocols for pedometer readings, but not for the calorie counter readings. The regression line between the calculated work load energy (y) and the calorie counter readings (x) was y= 1.73x + 5.05, with the calorie counter values being about 60% of the calculated standard. Although this device has some problems, it can be used to measure energy expenditure of exercise if exercise intensity is taken into consideration. It appears that this device provides more precise information of daily phyiscal activity that the pedometer.